1981
DOI: 10.1159/000176477
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hormonal Response to Chronic Maternal Fasting in the Ewe

Abstract: The purpose of this study was to investigate the metabolic adaptations of the fetus during maternal starvation and to determine the changes of plasma insulin and glucagon concentrations in the fed state and during severe maternal fasting in the chronic fetal sheep preparation. Maternal fasting resulted in a decrease in maternal and fetal plasma glucose as well as a decrease in fetal plasma fructose. Fetal-maternal arterial urea concentration differences increased with maternal fasting, suggesting increased fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Ep stein et al [12] found no increase in fetal glu cagon in the rhesus monkey made glucose intolerant with streptozotocin. Similar obser vations have been made in the fetal lamb, in which the concentration failed to change in response to fetal glucose infusion [15], In studies of chronic maternal fasting in the ewe, we found no significant change in the concentration of glucagon in fetal plasma during short-term fasting [37], but did find a trend towards an increased glucagon concen tration with a prolonged fast (more than 6 days) [36]. The purpose of this study was to investigate the effect of exogenous glucagon on fetal glucose, fructose and insulin in the sheep.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ep stein et al [12] found no increase in fetal glu cagon in the rhesus monkey made glucose intolerant with streptozotocin. Similar obser vations have been made in the fetal lamb, in which the concentration failed to change in response to fetal glucose infusion [15], In studies of chronic maternal fasting in the ewe, we found no significant change in the concentration of glucagon in fetal plasma during short-term fasting [37], but did find a trend towards an increased glucagon concen tration with a prolonged fast (more than 6 days) [36]. The purpose of this study was to investigate the effect of exogenous glucagon on fetal glucose, fructose and insulin in the sheep.…”
Section: Introductionsupporting
confidence: 87%
“…In 7 animals fetal samples only were obtained. Following a maternal fast of a minimum of 5 days, control values indicated that concentrations of glucose, fructose and insulin in fetal plasma were lower and of glucagon higher compared to the values when the ewe was fed, as has been pre viously reported [3,31,[35][36][37], Glucagon infusion into the fetus was then again per formed and the effects on the concentrations of glucose, fructose, insulin and glucagon in fetal plasma were similar to those found in the fed state. The fetal glucagon concentra tion ( fig.…”
Section: Fed Ewesmentioning
confidence: 87%
“…Hyperglycemia, probably secondary to acute glycogenolysis, was noted at all glucagon doses including I fLg/kg, achieving glucagon concentrations similiar to those found in states of chronic maternal fasting (23). Although this response was quantitatively less than that of the neonate, it could conceivably be of benefit in conditions of severe substrate depletion, particularly because in this state insulin secretio~i~at a minimum (23). Ketonemia was not noted after glucagon mJection and it is thus unlikely that endogenously elevated glucagon concentration would stimulate use of ketones as energy substrates acutely.…”
Section: Discussionmentioning
confidence: 59%
“…Numerous factors can modify the amplitude of these modifications in the metabolism and blood. For instance, the level of fasting ketonemia varies according to species (Bouchat, Doiz6 and Paquay, 1980 ;Brady et al, 1977 ; Schreiner, Lemons and Gresham, 1981 ;Williamson and Whitelaw, 1978 ;Zammit, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It may have a minor role in the genesis of fasting hyperketonemia in this species. A comparison can be made with ruminants in which glucagonemia increases only after prolonged fasting (Schreiner, Lemons and Gresham, 1981) and glucagon has a poor effect on ketogenesis from oleate in isolated liver cells (Donaldson and Pogson, 1983). The higher ketonemia in starved rabbits (fed the HF diet) could also have resulted from initially lower insulin levels, despite the fact that the difference was not significant (fig.…”
Section: Introductionmentioning
confidence: 99%